Cinderella liberator - Solnit, Rebecca (Haymarket Books, 2019)
In this modern twist on the classic story, Cinderella, who would rather just be Ella, meets her fairy godmother, goes to a ball, and makes friends with a prince. But that is where the familiar story ends. Instead of waiting to be rescued, Cinderella learns that she can save herself and those around her by being true to herself and standing up for what she believes.